Shariah standard for the adoption of artificial intelligence nanny: an analysis of potentials and challenges - Busari, Saheed Abdullahi; Sitiris, Miszairi (Department of Shariah and Law, Academy of Islamic Studies, UM, 2024)
Artificial Intelligence as the contemporary advanced technology is been gaining recognition in every sphere of life in recent times. The increasing economic activities of households have triggered demands for house maid as more people wanted the service of a house made to sustain their social family structure needs. Family experts have suggested that people’s demand for house maid depends on the value of their time. A hirer whose time is worth $10 per hour can afford to hire a house helper for $5 per hour. At this juncture, hiring a nanny has become a household necessity for many families due to busy schedules, dual-income lifestyles, physical limitations, specialized skill needs, caring for elderly or disabled family members, frequent travel, or enhancing the overall quality of life by outsourcing domestic tasks. However, the disruptive AI nanny may offer consistent monitoring, personalized education, house routine, and childcare assistance. It can also provide remote parent monitoring and emergency response; however, ethical and privacy considerations remain crucial to many households perceiving AI as a complement, not replace, tradition al caregiving. This study used the doctrinal approach of the qualitative method to critically analyze fundamental shariah standards required for the adoption of AI nannies. The study found that AI humanoid nannies in the contemporary can be considered as general items that can be adapted based on certain fundamental Shariah standards such as the intent of the operators, the social status of the AI nanny, the economic scale of producing AI nanny, the legal capacity of AI nanny and the physical features of AI nanny.